Contemporary approaches in the peri-endoscopic management of antithrombotic agents: current paradigms, challenges, and prognostications - Jiaxuan Zuo; Wei Jiang; Lumei Wang; Kaiqi Yang; Peng Li; Shutian Zhang; Rui Cheng (Therapeutic Advances in Gastroenterology, 2025)
With the increasing prevalence of endoscopic procedures, peri-endoscopic management of antithrombotic agents remains challenging due to inconsistent guideline adherence. This review highlights barriers to suboptimal guideline adherence, which include inadequate guideline education, delayed regional guideline updates, ambiguous anticoagulation responsibility, drug cost disparities, and uneven international resource allocation. Proposed strategies to improve compliance include: (1) Enhanced education for physicians and patients to align practices with evidence-based recommendations; (2) Digital tools such as clinical decision aids to standardize risk stratification and medication management; (3) Unified antithrombotic management teams to clarify responsibilities and reduce inter-specialty discrepancies; and (4) International collaboration to harmonize guidelines and address regional disparities in healthcare access and practice patterns. Existing guidelines from societies such as the European Society of Gastrointestinal Endoscopy, the American Society for Gastrointestinal Endoscopy, and the British Society of Gastrointestinal Endoscopy provide risk-stratified frameworks for procedure-specific antithrombotic management, yet their adoption varies globally. Eastern practices often prioritize shorter warfarin cessation windows (e.g., 3 days for routine colonoscopies in China), contrasting with Western protocols that align more closely with international guidelines. Future directions emphasize integrating artificial intelligence into clinical workflows to personalize risk assessments and adopting telemedicine platforms for real-time decision support. Addressing these gaps is critical to reducing thromboembolic and hemorrhagic complications in high-risk patients undergoing endoscopic procedures.